A Peri‐tetracene Diradicaloid: Synthesis and Properties - Ni, Yong; Gopalakrishna, Tullimilli Y.; Phan, Hoa; Herng, Tun Seng; Wu, Shaofei; Han, Yi; Ding, Jun; Wu, Jishan (Angewandte Chemie International Edition, 2018)
Peri‐acenes are good model compounds for zigzag graphene nanoribbons, but their synthesis is extremely challenging owing to their intrinsic open‐shell diradical character. Now, the successful synthesis and isolation of a stable peri‐tetracene derivative PT‐2ClPh is reported; four 2,6‐dichlorophenyl groups are attached onto the most reactive sites along the zigzag edges. The structure was confirmed by X‐ray crystallographic analysis and its electronic properties were systematically investigated by both experiments and theoretical calculations. It exhibits an open‐shell singlet ground state with a moderate diradical character (y0=51.5 % by calculation) and a small singlet–triplet gap (ΔES‐T=−2.5 kcal mol−1 by SQUID measurement). It displays global aromatic character, which is different from the smaller‐size bisanthene analogue BA‐CF3. Synthesis of peri‐tetracene done: A stable peri‐tetracene derivative was obtained in crystalline form. It has an open‐shell singlet ground state with a moderate diradical character. It shows amphoteric redox behavior with a small optical and electrochemical energy gap. It is magnetically active and exhibits a small single–triplet excitation energy. It is globally aromatic.